Sincronización los sistemas de investigación de la DIRINCRI con recursos móviles (smartphone) - Murga Cruces, William Walder (2018)
This research addresses the use of Google Cloud services with Firebase through the use of wired and wireless networks in the field of investigation of kidnappings of the Dirincri. The present thesis describes the reality of one of our most important institutions of our security, which is the area of kidnappings of the Dirincri which is a systematic, technical and specialized institution charged with investigating, denouncing and combating organized crime And other transcendental facts, has a great problem of information leakage which causes the obtained evidence to be accessible to personnel outside the division, which causes several cases to be closed due to lack of evidence or because they have already been intentionally eliminated, Peruvian state, innocent people involved in criminal acts and the personnel of the kidnapping division. The procedure is carried out by Third Party Technicians (Investigators), who receive the complaints to begin the investigation process; Which starts by analyzing the places taking different types of evidence (photos, videos, audios, tracks or information of what happened). Currently the DIRINCRI kidnapping department sends the data of each investigation by means of courier and social networks (Facebook, WahatsApp, Hotmail, Gmail, etc.), being these means very vulnerable to safeguard confidential information. For them we have applied for our analysis a methodology called Thinking which we applied to be able to determine the problem in a more dynamic way and which resulted in us not having a modern and reliable means to send and access information in time Real and that is lodged in the cloud to be able to download it at any time and on the condition that it is the most confidential and to avoid the use of other public systems already mentioned previously. The proposed solution consists of synchronizing the Dirincri Research Systems with Smartphone, which will allow us to use the networks (Internet), Google Cloud Firebase Services, Network Protocols and App (Android) With these tools we will realize and exploit the current resources that today India is part of our daily lives; These tools will allow to capture and send the information of the investigations and save them in a repository to which only members of the division of abductions with their respective credentials can accede. For them we will use the service of Google Cloud which has a platform called Firebase which is a database and one of the most used in the market and with the confidentiality that is required for information on the subject of security and efficiency in Synchronization we will use the personnel records. What we are looking for is to exploit communications networks with the help of platforms such as Cloud services and App development that are allowing us to exploit our communications networks over the last 10 years, and which are part of our lives.